(untitled) (International Journal of Engineering and Computer Science, 2018)
Documents on the web exist in digital format, people spend large amount of time on searching using web browsers for finding useful information. The results returned by search engines are in the form of web pages that contains results obtained from different web databases. These results can be used further in many applications such as data collection, comparison of prices and many more but to make these applications successful the search results should be machine processable. so to make them machine processable, it is important that the result pages are annotated in a meaningful manner. The process of annotating has to consider groups of data and obtain final annotation after aggregating them. Annotation can be done for the Web, java, pdf files, text files, xps, mobile, image, multimedia etc. In Information retrieval for decision support and integrating an annotation database can be founded on the parameters such as document, user and time. Automatic extraction of the data from querying result pages is very much important for different applications, such as data integration, Meta querying cooperates with multiple web databases.